(3GdPcGA GdTYhQj aj GdefXeGJ (B:s (3eONd eJcGed (B/s - (3GdWGFj, jhSa MLje SdWGfs; (3GdYWhj, YGeQ Ydj MSjf s ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B, s, 2010)
(3fTCI GdPcGA GdTYhQj, eQGMd JWhQg h ejGOjf OQGSJg h GdWHjYI GdYVhjI dg, GdPcGA GdTchQj ddaQO h NUGFU eQJaYj h efNaVj GdPcGA GdTYhQj, feGPL h ebGjjS GdPcGA GdTYhQj ddaQO, feGPL h ebGjjS GdPcGA GdTYhQj ddaQjb h JWhQ gPG GdPcGA aj GdefXeI h CNjQG GdPcGA GdTYhQj ddbGFOs
Keywords: (3GdPcGAs; (3GdSdhc GdEOGQjs; (3Yde GdfaS GdJWHjbjs